Innovative Pedagogies in Musical Education: Integrating Technology for Enhanced Learning Outcomes (Música Hodie, 2025)
The aim of this article is to examine the effectiveness of innovative pedagogy in music education through the integration of digital technologies in piano instruction. The training was conducted with students who were taught using an innovative method (Group 1) and a traditional system (Group 2). The innovative training incorporated digital applications such as Pianote, Smart Pianist, Firehawk, and Music Piano Master. The educational process aimed to develop students' motor skills in piano playing, explore stages of working on musical pieces, enhance melody intonation skills, and increase the complexity of musical compositions. To evaluate student performance, the Gold-MSI v.1.0 test was employed, reflecting the level of musical information acquisition by the students. Group 1 students demonstrated higher performance according to the Gold-MSI v.1.0 test criteria. The calculation of Cronbach's alpha coefficient indicated that Group 1 students achieved high levels of musical skills (0.792), musical engagement (0.903), professional competence (0.867), emotional responsiveness to music (0.881), and overall musical development (0.849). It was found that 89% of Group 1 students confirmed the high quality of such training, emphasizing creativity and a systematic approach. In contrast, 53% of Group 2 students rated the training as neutral, which was associated with a lack of motivation. The practical significance of this work lies in the potential adaptation of the applied approaches to piano instruction for a larger number of students through the use of various digital applications.